ANALISIS KUALIFIKASI, KOMPETENSI TUTOR/PENDIDIK DAN PROFIL PENGELOLA PENDIDIKAN KESETARAAN PADA PKBM DI DKI JAKARTA - Sutisna, Anan (JIV-Jurnal Ilmiah Visi, 2011)
The purpose of this study is to describe the data of the educational qualification, tutor’s competence, and the administrators in equalizing education. This study is based on the fact tutors and the executing staff play a very important role in improving the instructional services. The study employed survey method with descriptive technique and questionaire. The study took place in PKBM in Jakarta on April to September 2011, with the research subjects include tutors and administrators. The findings indicate that the tutor’s qualification has met the requirement but there is a mismatch between the educational specialization and the courses to teach, the tutor’s competence is regarded low (at the average of 37,3) in pedagogy and andragogy and the administrators consist of head, secretary, and administrative staff as well as the educational staff.